Lipoprotein(a) and High Sensitivity C-Reactive Protein among Patients with HIV in Ghana: The Study on Cardiovascular Risk Profile of HIV-Infected Patients on HAART (SCRIPT). Issue 1 (3rd November 2020) - Appiah, Lambert Tetteh; Sarfo, Fred Stephen; Nguah, Samuel Blay; Huffman, Mark D.; Stiles, Jonathan K.; Feinstein, Matthew J.
Background: Lipoprotein(a) [Lp(a)] and high-sensitivity C-reactive protein (hs-CRP) levels are associated with cardiovascular disease (CVD) in the general population, even after adjusting for conventional CVD risk factors. However, data are limited regarding the distribution of Lp(a) and hs-CRP among patients with HIV in Ghana. We explored levels of Lp(a), hs-CRP and other cardiovascular risk factors among people who were HIV positive (HIV+) on ART (HIV+ART+), HIV+ART–, and HIV–ART– in a Ghanaian population. Methods: We conducted a cross sectional study, recruited individuals who were HIV+ART+ and HIV+ART– from the largest HIV clinic in central Ghana between August 2018 and December 2019. HIV negative controls were recruited from communities and adjoining suburbs of Kumasi. Lipoprotein(a) was measured using Immunoturbidimetric assay and high sensitive-CRP concentrations were determined using particle-enhanced turbidimetric assay. We compared levels of Lp(a), hs-CRP, and conventional CVD risk factors among these groups and used multivariable stepwise logistic regression models to explore associations between them. Results: Among HIV+ART+ (n = 156), HIV+ART– (n = 131), and HIV–ART– (n = 147), mean(SD) ages were 48 (9.1) years, 41 (11.1) years and 45 (11.9) years, p = <0.001, proportion of females were 71.2%, 67.9% and 73.5% respectively. Median(IQR) concentrations of hs-CRP in mg/L were 1.7 (0.8, 4.5), 2.03 (0.5, 8.58) and 1.0 (0.45, 2.74) across respective groups and the proportion of elevated Lp(a) concentrations (Lp[a] > 30mg/dL) were 70%, 48% and 62% among HIV+ART+, HIV+ART– and HIV–ART– participants respectively. Diabetes mellitus, dyslipidemia, waist-to-hip ratio and metabolic syndrome were associated with higher hs-CRP levels. Compared to HIV–ART–, HIV+ patients had higher odds of having hs-CRP > 3mg/L while HIV+ART+ patients had higher odds of elevated Lp(a) than HIV+ART– after multivariable adjustment. Conclusion: PLWHA in Ghana are associated with higher odds of elevated hs-CRP, regardless of ART use. HIV+ART+ is significantly associated with higher odds of elevated Lp(a) levels compared to HIV+ART–; even after multivariable adjustments. Reasons for this and potential clinical implications merit further study.